Significant learning and tasks integrated in the classroom - Martínez Lobato, Esteban (Avances en Supervisión Educativa, 2014)
A competency-based approach is an "educational revolution" for some teachers, it calls into question traditional teaching practices. Cause significant learning requires actively involve the student in search processes, study, experimentation, reflection, application and communication of knowledge. Required to work regularly and integrated tasks located in different contexts, which are used in knowledge (knowledge, procedures and attitudes) and to mobilize resources to achieve competence learning, meaningful and functional based on the resolution of problem situations or projects , is a function and relevance of the content and use of new resources (ICT) and other forms of assessment, etc.. In the present communication is to orient teachers to place the student organized integrated tasks and competences, to develop new and varied situations so as to mobilize and exercise their competence to resolve a problem, make decisions, take carry out projects or reports and communications, projections, creation and production ..., which resulted in significant and socially relevant.